Infrastructure Revitalization, MSME Empowerment, and Socio-Cultural Education through the Community Outreach Program (COP) in Rejosari Village, Mojokerto - Aplonia Nelci; Jellytha Tani, Fransiska; Shintya Namu Ago, Kristina; Verouden, Meike; Yanagimoto, Yuna; Candra Sanjaya, Vania; Djuanda, Evelyn; odriques, Servatius (IJECS: Indonesian Journal of Empowerment and Community Services, 2026)
ABSTRACT This community service program was conducted through the Community Outreach Program (COP) in Rejosari Village, Mojokerto, East Java. The program aimed to support village development through integrated activities focusing on infrastructure revitalization, micro small and medium enterprise (MSME) empowerment, and socio-cultural education. Using a multinational service-learning approach, the program involved 26 students from six countries who collaborated with local stakeholders to address community needs through both physical and non-physical interventions. Key activities included the revitalization of community facilities, improvement of fishpond infrastructure, environmental arrangement, MSME rebranding, and socio-cultural and cultural exchange activities for children and community members. The results indicate improvements in the functionality of village infrastructure, increased readiness of local MSMEs to market their products, and enhanced community participation in social, educational, and cultural activities. The program also fostered cross-cultural understanding and collaboration between local residents and international participants. Although the implementation period was relatively short, the outcomes demonstrate that an integrated and multicultural community service model can contribute positively to local capacity building and community engagement. The COP Rejosari program offers a practical and replicable model for holistic community development in rural areas with similar characteristics. Keywords: Product Rebranding; Rural MSMEs; Community Empowerment; Infrastructure Revitalization; Community Outreach Program